Opportunities and Potentials of Mobility as a Service After the Corona Pandemic - Benedikt Scheier; Benjamin Frieske; Kathrin Viergutz (Wirtschaftsdienst)
Abstract The pandemic represents a break in the positive development of public transport. The users’ fear of infection could have a lasting negative effect on public transport. This article presents the opportunities and potentials of mobility as a service, with a focus on demand responsive transport. Particular opportunities could lie in a vehicle concept with exclusive compartments, which also have advantages over conventional public transport vehicles in terms of infection protection. Acquisition and ownership costs are determined on the basis of an operating simulation.